Dose intense chemotherapy in the management of poor prognosis and relapsed testicular cancer: experiences and controversies. Issue 5 (4th May 2018) - Ng, Kenrick; Duncan, Sarah; Shamash, Jonathan; Alifrangis, Constantine
ABSTRACT: Introduction : The treatment of poor prognosis chemotherapy naïve or relapsed testicular cancer is challenging. In poor prognosis treatment naïve disease, the outlook for patients with standard approaches utilising three weekly cisplatin based regimens, most commonly bleomycin, etoposide and cisplatin (BEP) is suboptimal, and one can expect more than half of patients to relapse or progress and need salvage treatment. Recent randomised studies have lent weight to the use of dose intensified treatments in these selected patient groups. In relapsed testicular cancer, post platinum based chemotherapy controversy exists as to the optimum relapse regimen as significant cure rates can be expected by re-treating with both conventional dose and high dose or dose intense regimens. Areas covered : This review seeks to outline the evidence for alternative approaches beyond standard three weekly cisplatin based regimens in poor risk metastatic disease. It also explores the evidence available for selection between conventional dose and high dose strategies on relapse. Expert commentary : An overview of the data is presented to support personalising therapy selection in both poor risk and relapsed metastatic germ cell tumors.